JS1.2 Increased frequency of paraneoplastic encephalitis with anti-Ma2 antibodies in the cancer immunotherapy era. (6th September 2019) - Vogrig, A; Fouret, M; Joubert, B; Picard, G; Rogemond, V; Pinto, A; Muñiz Castrillo, S; Roger, M; Raimbourg, J; Dayen, C; Grignou, L; Pallix-Guyot, M; et al.
Abstract: BACKGROUND: Given the mechanism of action of immune checkpoint inhibitors (ICIs), a possible association with the development of paraneoplastic neurological syndromes (PNS) has been hypothesized. We sought to determine if ICI treatment might trigger anti-Ma2 antibody-associated paraneoplastic neurological syndromes (Ma2-PNS). MATERIAL AND METHODS: We performed a retrospective nationwide study of all patients with Ma2-PNS developed during ICI treatment between 2017–2018. The frequency of neuronal-antibody detection before and after ICI implementation was also analyzed. RESULTS: Our series of patients included 5 men and 1 woman (median age, 63 years). The patients were receiving either nivolumab (n = 3), pembrolizumab (n = 2) or a combination of nivolumab and ipilimumab (n=1), for treatment of neoplasms that included lung (n=4) and kidney (n=1) cancers, and pleural mesothelioma (n=1). Median delay between ICI introduction and onset of the neurological syndrome was 4 months. Clinical syndromes included a combination of limbic encephalitis and diencephalitis (n=3), isolated limbic encephalitis (n=2) and a syndrome characterized by opthalmoplegia and head-drop (n=1). Patients with diencephalitis manifested hyperphagia, weight gain and somnolence. Post-ICI Ma2-PNS accounted for 35% of the total 17 Ma2-PNS diagnosed in our center over the 2017–2018 biennium. Eight cases had been detected in the preceding biennium 2015–2016, corresponding to a 112% increase of Ma2-PNS frequency since the implementation of ICIs in France. No other neuronal-antibody demonstrated a similar increment. CONCLUSION: We show a clear association between ICI use and increased frequency of Ma2-PNS. Physicians need to be aware that ICIs can trigger Ma2-PNS since clinical presentation can be challenging.